1999
DOI: 10.1046/j.1365-2494.1999.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of phosphorus, potassium, lime and molybdenum on the growth and morphology of white clover (Trifolium repens L.) at establishment

Abstract: The effects of simultaneously varying P, K, lime and Mo supplies on the growth and shoot morphology of white clover (Trifolium repens) at establishment were investigated in a factorially designed glasshouse experiment. Phosphorus and lime applications had almost identical, additive, effects on dry‐matter (DM) production, and it was clear that the benefit of both treatments lay in the resultant improvements in plant available P. The adverse effects of P deficiency on young plants resulted, immediately, in a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Turner (1990) suggested that clover has poor stomatal control of leaf hydration and water loss, and stomatal closure may be incomplete even when turgor is low, thus verifying white clover susceptibility to water deficits. Bailey and Laidlaw (1999) reported that soil pH < 6.0 and adverse effects of phosphorous (P) deficiency on young plants resulted immediately in a large reduction in stolon branch numbers. Thus, survival of white clover in swards at establishment is critically dependent on P supply, and that one of the main benefits of liming is the resultant improvement in P availability.…”
Section: Growth and Persistencementioning
confidence: 99%
“…Turner (1990) suggested that clover has poor stomatal control of leaf hydration and water loss, and stomatal closure may be incomplete even when turgor is low, thus verifying white clover susceptibility to water deficits. Bailey and Laidlaw (1999) reported that soil pH < 6.0 and adverse effects of phosphorous (P) deficiency on young plants resulted immediately in a large reduction in stolon branch numbers. Thus, survival of white clover in swards at establishment is critically dependent on P supply, and that one of the main benefits of liming is the resultant improvement in P availability.…”
Section: Growth and Persistencementioning
confidence: 99%
“…Increasing soil pH improves molybdenum availability and encourages better clover performance, since molybdenum is required for nodulation in clover. 36 Speci®cally, clover nodules require molybdenum as a component of nitrogenase enzymes. 37 The greater concentration of iron, manganese, cadmium, aluminium and nickel in grass compared with clover (Table 1) may derive from the reduced competitiveness of clover in grass±clover mixtures, which is due primarily to its uncompetitive root morphology.…”
Section: Herbagementioning
confidence: 99%
“…Molybdenum, which constitutes part of the enzyme nitrogenase, is also essential for symbiotic nitrogen fixation; Mo deficiencies are therefore much more pronounced in legumes (Bailey & Laidlaw, 1999). Since peanut is a legume, it is highly susceptible to Mo deficiency when grown in acidic soils.…”
Section: Introductionmentioning
confidence: 99%
“…Since peanut is a legume, it is highly susceptible to Mo deficiency when grown in acidic soils. This affects its ability to nodulate and symbiotically fix atmospheric nitrogen (Simbajon & Duque, 1987;Bailey & Laidlaw, 1999). This study, therefore, investigated the effect of lime and molybdenum and their interaction on peanut yields on a low pH soil.…”
Section: Introductionmentioning
confidence: 99%